2018
DOI: 10.3389/fnhum.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Influences the Recruitment, but Not Structure, of Muscle Synergies

Abstract: The development of fatigue elicits multiple adaptations from the neuromuscular system. Muscle synergies are common patterns of neuromuscular activation that have been proposed as the building blocks of human movement. We wanted to identify possible adaptations of muscle synergies to the development of fatigue in the upper limb. Recent studies have reported that synergy structure remains invariant during the development of fatigue, but these studies did not examine isolated synergies. We propose a novel approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
6
27
0
Order By: Relevance
“…Animal (Tresch and Bizzi 1999;Bizzi et al 2008;Hart and Giszter 2013) and computational (Neptune et al 2009) models using electrical stimulation support a neural origin for muscle synergies. Similarly, human experiments are consistent with a neural origin of muscle synergies during natural movements (d'Avella and Bizzi 2005;Safavynia and Ting 2012), affecting learning rates (Berger et al 2013;Sawers et al 2015), for postural control (Weiss and Flanders 2004), when extracted from the frequency domain (Frere 2017), irrespective of muscle fatigue (Ortega-Auriol et al 2018), and in the presence of CNS damage after stroke (Cheung et al 2009;Berger et al 2013). Conversely, evidence for muscle synergies as a result of purely mechanical constraints arise from computer simulations of the upper arm movement on a single plane (Inouye and Valero-Cuevas 2016) and cadaveric studies (Kutch and Valero-Cuevas 2012).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Animal (Tresch and Bizzi 1999;Bizzi et al 2008;Hart and Giszter 2013) and computational (Neptune et al 2009) models using electrical stimulation support a neural origin for muscle synergies. Similarly, human experiments are consistent with a neural origin of muscle synergies during natural movements (d'Avella and Bizzi 2005;Safavynia and Ting 2012), affecting learning rates (Berger et al 2013;Sawers et al 2015), for postural control (Weiss and Flanders 2004), when extracted from the frequency domain (Frere 2017), irrespective of muscle fatigue (Ortega-Auriol et al 2018), and in the presence of CNS damage after stroke (Cheung et al 2009;Berger et al 2013). Conversely, evidence for muscle synergies as a result of purely mechanical constraints arise from computer simulations of the upper arm movement on a single plane (Inouye and Valero-Cuevas 2016) and cadaveric studies (Kutch and Valero-Cuevas 2012).…”
Section: Introductionmentioning
confidence: 54%
“…EMG processing: The processing of multidirectional trials for synergy extraction is described in detail in our previous research (Ortega-Auriol et al 2018). Briefly, EMG signals were: trimmed for the intermediate two seconds of the target match period, band-pass filtered (bidirectional Butterworth, 2 nd order, 5-400 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, pre-processing could be a source of data misinterpretation. Furthermore, the insurgence of fatigue was not inspected in this study, while it was demonstrated in the literature that fatigue may influence the recruitment of synergies, even if their spatial composition is preserved (Ortega-Auriol et al, 2018 ). As described in the section Introduction, several factors may have an effect on sEMG signal and make synergies tough to be generalized.…”
Section: Discussionmentioning
confidence: 85%
“…Few studies addressed these effects until now, and the effect on the resulting muscle synergies. Considering upper limb synergies, Ortega et al observed that synergy structure was conserved with fatigue, but interestingly synergy activation coefficients decreased on average by 24.5% with fatigue development (Ortega-Auriol et al, 2018 ). In Tagliabue et al ( 2015 ) two-digit grasping is analyzed.…”
Section: Introductionmentioning
confidence: 99%